2013
DOI: 10.5812/atr.10338
|View full text |Cite
|
Sign up to set email alerts
|

Acromioclavicular Joint Fixation Using an Acroplate Combined With a Coracoclavicular Screw

Abstract: BackgroundAppropriate treatment of acromioclavicular joint dislocation is controversial. Acroplate fixation is one of the most common treatment methods of acromioclavicular joint (ACJ) dislocation. Based on the risk of re-dislocation after Acroplate fixation, we assumed that combined fixation with an Acroplate and a coracoclavicular screw helps improve the outcome.ObjectivesThe main purpose of the current study was to compare the outcome of ACJ dislocation treated with an Acroplate alone and in combination wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Since Rockwood's classification of ACJ is based on the degree and direction of clavicle displacement, reconstruction of the CC ligament is the most commonly applied clinical surgical strategy 3,4 . Although Bosworth screws have been reported in the literature in addition to the five surgical procedures included in this study, after a careful review of the literature we found that few studies met the criteria and no valid data were available 55–57 . Notably, in addition to CC reconstruction, AC reconstruction (tension band wires, Kirschner wires, or sutures), 8,58 AC and CC reconstruction (Weaver–Dunn procedures) 59 are also options for surgical treatment.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Since Rockwood's classification of ACJ is based on the degree and direction of clavicle displacement, reconstruction of the CC ligament is the most commonly applied clinical surgical strategy 3,4 . Although Bosworth screws have been reported in the literature in addition to the five surgical procedures included in this study, after a careful review of the literature we found that few studies met the criteria and no valid data were available 55–57 . Notably, in addition to CC reconstruction, AC reconstruction (tension band wires, Kirschner wires, or sutures), 8,58 AC and CC reconstruction (Weaver–Dunn procedures) 59 are also options for surgical treatment.…”
Section: Discussionmentioning
confidence: 92%
“… 3 , 4 Although Bosworth screws have been reported in the literature in addition to the five surgical procedures included in this study, after a careful review of the literature we found that few studies met the criteria and no valid data were available. 55 , 56 , 57 Notably, in addition to CC reconstruction, AC reconstruction (tension band wires, Kirschner wires, or sutures), 8 , 58 AC and CC reconstruction (Weaver–Dunn procedures) 59 are also options for surgical treatment. However, the literature on AC reconstruction is scarce and valid data are not available.…”
Section: Discussionmentioning
confidence: 99%